KECERDASAN BUATAN (AI) DALAM AUDIT LAPORAN KEUANGAN SYARIAH:TREN DAN TANTANGAN - Jedlisaputra; Vivi Nurul Alfia; Dzakira isratun Nisa (Journal of Islamic Economics and Finance, 2025)
This abstract discusses the use of artificial intelligence in auditing Islamic financial statements, The goal is to not only evaluate the accuracy of the statements but also to ensure that they are in accordance with Islamic principles, such as honesty, fairness, and the prohibition of usury. With technologies such as machine learning and natural language processing, analysis of transactions and contracts can be done quickly and thoroughly. Artificial intelligence supports auditors and the sharia supervisory board in identifying non-halal transaction and checking compliance with fatwas from the DSN-MUI. However, there are major challenges, such as the lack of bias in the algorithm. Collaboration between technology experts, academics, and scholars is needed to create an artificial intelligence audit system that is ethical, transparent, and in line with the maqasid of sharia.